Language, Power, and Crime: A Discourse Analysis of Murder Reporting in Kenyan Newspapers - Elizabeth Khaemba; Simon Nganga; Stellah Onyiego (CV. Rustam, 2026)
This paper explores the linguistic strategies used by journalists in reporting murders implicating prominent personalities. Notably, it examines how these strategies are employed to construct the perpetrators’ identities, underscoring how journalists navigate the power dynamics inherent in such stories while managing potential harm to themselves, the subjects involved, and the broader sociopolitical context. The critical role of language in shaping public discourse on justice is also examined. Utilizing ten purposively sampled headlines and leads from The Daily Nation and The Standard newspapers’ 2018 coverage of murders implicating prominent figures in Kenya, a qualitative investigation reveals how journalists negotiate power asymmetries and the implications of this navigation for both their safety and public perceptions of justice. Guided by Roger Fowler’s Critical Linguistics (1970), the findings indicate that journalists employ nominal references and transitivity choices differently, depending on the subject’s status and the media outlet. There’s a notable tendency for the Daily Nation to use both nominal references and transitivity to implicate suspects, thereby emphasizing accusation and implicitly reinforcing a narrative of guilt. Conversely, The Standard’s use of similar strategies tends to deflect blame, offering protection to suspects. These divergent patterns raise essential questions about media framing, power asymmetries in crime reporting, and highlight the need for policy and advocacy efforts to foster ethical and balanced journalism. Recommendations include investigating digital and audio media, as well as cases involving less powerful individuals, to deepen our understanding of how language mediates issues of justice and inequality across various platforms.